Did Developed and Developing Stock Markets React Similarly to Dow Jones During 2008 Crisis? - Özen, Ercan; Tetik, Metin (Frontiers in Applied Mathematics and Statistics, 2019)
The aim of this study is to determine whether the stock indices of some developed and developing countries react similarly to the price movements in the Dow Jones Industrial Average (DJIA). In this study, the impact of DJIA on other indices during the 2008 global financial crisis, was explored by using the Vector Error Correction Model. The data used was analyzed in two periods: 1) the expansionary period; and 2) the contractionary period of the FED’s policies. The results of the analysis indicate that the developed and emerging stock markets react differently to the DJIA. The results include important findings for decisions by financial investors and policy makers.